Portrait of Teacher Competence and Implementation Challenges of Achieving Sustainable Development Goals (SDGs): A Comparative Study between Indonesia and Vietnam - Mohammad Firdaus; Zainul Fuad; Kusaeri; Evi Fatimatur Rusydiyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Teachers need to update their competency profiles to face the challenges of implementing sustainable development goals (SDGs). Teaching strategies need to change and so do the competencies that teachers need to develop to face the implementation of achieving sustainable development goals. Teacher competency improvement training programs in Indonesia and Vietnam are paradigmatic examples of efforts to produce quality education, taking into account these needs. Teacher competencies can serve multiple purposes at various levels in the education system. This systematic literature review study was organized using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Guidelines for reporting the event evaluated by teacher competence in the challenges of implementing the achievement of sustainable development goals (SDGs), This review study sought and analyzed descriptive data (case reports and cross-sectional studies) on teacher competence and SDGs. All data must be in the form of Sinta and Scopus indexed research results, 30 Data searches were conducted from November 2022 on SEForA, Publish or Perish, ERIC, and ScienceDirect search engines and websites, using relevant keywords teacher competencies, SDGs, education, Indonesia, and Vietnam using English. Findings Teacher competencies in the SDGs state that competencies are inherent and integrated to teachers, teachers are important to have pedagogical competence and professional competence as the main qualification requirements for carrying out tasks or work in educating students. Keywords: Teacher Competence, Achieving Sustainable Development Goals